Exploring Kohak’s Dialogue With Nature as a Language Game - Sedlar, Matej (Cosmos and History: The Journal of Natural and Social Philosophy, 2023)
The article provides a textual analysis of Kohak’s position on human relationship with the natural world, through the lens of Wittgenstein’s language games. The experiential engagement of humans and their perception of the natural world is analysed as a language game of its own, featuring the interplay between the contrasting phenomenological perspectives on the human role in the Earths functioning; humans qua members of the ecosystem and humans as entities outside of it which shape it to their will. The article then claims that by perceiving our interactions with nature in its entirety as a language game, our internal perspective on our relationship will by necessity constitute the former one, which in turn provides for a normative shift towards taking into account nature’s needs and wants. In other words, the article provides an argument for changing our views on nature towards a relationship of ethical equality, which is essential for dealing with issues pertaining to the environment reasonably.